Highly Efficient Biotransformation of Phenolic Glycosides Using a Recombinant β-Glucosidase From White Rot Fungus Trametes trogii - Qu, Yuan; Luo, Yuan; Yang, Xulei; Zhang, Yu; Yang, En; Xu, Huini; He, Yingying; Chagan, Irbis; Yan, JinPing (Frontiers in Microbiology, 2022)
Phenolic glycosides are the important bioactive molecules, and their bioavailability can be influenced by enzyme hydrolysis, such as β-glucosidases (EC3.2.1.21) and other glycosyl hydrolases (GHs). Wood rotting fungi possess a superfamily of GHs, but little attention has been paid to the GHs and their potential applications in biotransformation of phenolic glycosides. In this study, two GH3 gene family members of Trametes trogii S0301, mainly expressed in the carbon sources conversion stage were cloned, and TtBgl3 coded by T_trogii_12914 showed β-glucosidase activity toward 4-nitrophenyl β-D-glucopyranoside (pNPG). The recombinant TtBgl3 preferred an intermediately neutral optimum pH with > 80% of the maximum activity at pH 5.0-7.0 and was stable at a wide range of pH (5.0-10.0). Phenolic glycosides transformation experiments showed that TtBgl3 was a dual-activity enzyme with both activities of aryl-β-D-glucosidase and β-glucuronidase, and could hydrolyze the β-glucoside/glucuronide bond of phenolic glycosides. Under optimized conditions, the recombinant TtBgl3 had much higher transformation efficiency toward the β-glucoside bond of gastrodin, aesculin and daidzin than β-glucuronide bond of baicalin, with the transformation rate of 100% and 50%, respectively. Our homology modeling, molecular docking, and mutational analysis demonstrated that His85 and Lys467 in the acceptor-binding pocket of TtBgl3 were the potential active sites. The point mutation of His85 and Lys467 leads to the significantly impaired catalytic activity toward pNPG and also the weak transformation efficiency toward gastrodin. These findings provide insights for the identification of novel GH3 β-glucosidases from T. trogii and other wood-rotting fungi. Furthermore, TtBgl3 might be applied as green and efficient biological catalysts in the deglycosylation of diverse phenolics to produce bioactive glycosides for drug discovery in the future.